Measuring progress towards sustainable development in Venice: A comparative assessment of methods and approaches - Julie Catherine Sors (Fondazione Eni Enrico Mattei (FEEM), 2001)
Sustainable development is a relatively well-known concept. Although there are many definitions, the underlying concepts and aims are generally agreed upon. Many local communities have established a 'vision' of sustainability in terms of policies, goals, actions, etc in order to translate sustainability into their own context. Since sustainable development is an ambitious and long-term goal, it is clear that it is important to be able to assess the degree of progress towards it. This is a particularly challenging task for the city of Venice due to its unique environmental, social and economic characteristics.This overview is intended to discuss and compare the main approaches to measuring progress in order to propose a methodology for Venice. Five methods which represent the spectrum of approaches are analysed. Finally, the potential applicability of these to Venice are considered in light of the specific conditions of the city, and a set of local sustainability indicators is proposed.
Keywords: I20; J18; 330; Measuring progress; sustainable development; sustainability indicators; Barometer of Sustainability; Ecological Footprint; Nachhaltige Entwicklung; Sozialer Indikator; Messung; Theorie; Venedig